Assessing Internet Use in Florida Newsrooms - Emily B. Rhoades; Tracy Irani; Ricky Telg (Journal of Applied Communications, 2005)
The Internet has become a major factor in the mass media industry. As a consequence, information sources, including agricultural communicators, are considering the decision to move to Web-based publications and publicity dissemination tools. Rural and agricultural audiences, however, have favored traditional media as a source of news and information, creating something of a “rural-urban digital divide.” In an attempt to assess how mass media news operations are utilizing the Web as a newsgathering and information source, a statewide descriptive survey was conducted of a random sample of local and regional media outlets. Results showed that television, radio, and newspaper newsrooms were using computers and the Internet extensively not only for receiving information and research but also for disseminating news. Respondents indicated that 88.9% of reporters used the Internet on a daily basis, while 72.2% of news units maintain an online presence. These findings indicate that as media outlets increase their utilization of the Web, agricultural industries and higher education institutions need to move more to electronic dissemination of information.